Peter Paul Rubens (1577-1640) and his landscapes : ideas on nature and art - Kleinert, Corina (Pictura nova, 2014)
Painting landscapes was very much a private activity for Peter Paul Rubens. Whilst the majority of his other works were commissioned, the landscapes seem to have been painted for his own pleasure and delight and stayed in the artist's possession until his death. Most of them were painted in the last decade of his life, a happy period, in which Rubens retired from public duties and spent most of his free time studying the antique and enjoying sojourns on his country estate, castle Het Steen. To grasp this profoundly personal character of Rubens's landscapes, this book considers the artist's highly complex method of pictorial invention to illuminate the perception, implementation, dissemination, and posthumous reception of views on nature and landscape as depicted in Rubens's landscape art